Modernisme as a Movement in Arabic Literature - Dedi Saputra; Anshar Zulhelmi; Salsabiela Syifa Anies; Nuril Rinahayu (Pusaka Cendekia Indonesia Foundation, 2025)
This research aims to explain modernism as one of the genres in Arabic literature, which has been more often understood in the framework of periodization than as a literary genre. This study uses a descriptive qualitative method with a literature study approach. Data was obtained from various written sources in the form of books and scientific articles that discuss literary genres, modernism, and the development of modern Arabic literature. The results of the study show that modernism is a literary school that was born in response to social, political, and intellectual changes, especially after World War I, which was marked by a humanitarian crisis and a shift in traditional values. In the context of Arabic literature, modernism developed along with the revival (nahḍah), the intensity of contact with the West, the advancement of education, and the role of the press in spreading new ideas. Modernism in Arabic literature is characterized by characteristics such as individualism, experimentation with form, absurdity, symbolism, and formalism. Thus, modernism reflects not only the renewal of literary forms and styles, but also the change in the way Arab writers view the function of literature in modern society. Penelitian ini bertujuan untuk menjelaskan modernisme sebagai salah satu aliran dalam sastra Arab, yang selama ini lebih sering dipahami dalam kerangka periodesasi dibandingkan sebagai aliran sastra. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi pustaka. Data diperoleh dari berbagai sumber tertulis berupa buku dan artikel ilmiah yang membahas aliran sastra, modernisme, serta perkembangan sastra Arab modern. Hasil kajian menunjukkan bahwa modernisme merupakan aliran sastra yang lahir sebagai respons terhadap perubahan sosial, politik, dan intelektual, khususnya pasca Perang Dunia I, yang ditandai oleh krisis kemanusiaan dan pergeseran nilai-nilai tradisional. Dalam konteks sastra Arab, modernisme berkembang seiring dengan kebangkitan (nahḍah), intensitas kontak dengan Barat, kemajuan pendidikan, dan peran pers dalam menyebarkan gagasan-gagasan baru. Modernisme dalam sastra Arab ditandai oleh karakteristik seperti individualisme, eksperimen bentuk, absurditas, simbolisme, dan formalisme. Dengan demikian, modernisme tidak hanya mencerminkan pembaruan bentuk dan gaya sastra, tetapi juga perubahan cara pandang sastrawan Arab terhadap fungsi sastra dalam masyarakat modern.